EVALUATION OF DIFFERENT RICE VARIETIES FOR GROWTH AND YIELD CHARACTERISTICS - S. Hussain; T. Fujii; S. McGoey; M. Yamada; M. Ramzan; M. Akmal (Journal of Animal and Plant Sciences, 2014)
Crop genotypes play a dominant role in crop production systems. They affect crop productivity by their higher yield potentials, resistance against insect pest and diseases under different climatic conditions. To evaluate different varieties of rice for their growth and yield characteristics, an experiment was conducted during 2012. Four varieties including IR-28, NERICA-4, Koshihikari and Nipponbare were evaluated in a randomized complete block design (RCBD) with three replications. All varieties were transplanted at spacing of 30x15 cm using 3 seedlings / hill. Data on various growth and yield parameters revealed that Koshihikari was the tallest (117 cm) and Nipponbare the shortest one (102 cm). Japonica varieties produced higher number of tillers/m2, dry weight (t/ha), LAI, number of panicles/m2, ripening ratios and lower nitrogen contents in panicle, stem and leaves. NERICA-4 gave higher values of SPAD, number of spikelets/ panicle (106) and harvest index (0.47). The highest straw weight (11.53 t/ha) and paddy yields (6.79 t/ha) were obtained from IR-28. The lowest values of harvest index (0.37) were also recorded from IR-28. Japonica and IR-28 produced higher paddy yields than NERICA-4 (5.77 t/ha) so they can be cultivated successfully under temperate climatic conditions.
Keywords: Varieties; Productivity; Characteristics